Asuhan Kebidanan Pada Bayi Baru Lahir Normal Di PMB Nelly Suryani Wilayah Kerja Puskesmas Kuok - Fadilah, Nuraisyah; Dhilon, Dhini Anggraini (Evidence Midwifery Journal, 2024)
Normal newborns are babies born spontaneously with a percentage of the back of the head passing through the vagina without using tools, at a gestational age of 37 weeks-42 weeks, with a body weight of 2500 grams-4000 grams, an APGAR score of more than seven and no congenital disorders. The aim of the research is to provide midwifery care to normal newborn babies at (Independent Midwife Practice) PMB Nelly Suryani in the Kuok Health Center Work Area on June 14 – June 22 2024. The results of the case study research were given to By. A With 3 home visits in 8 days, the mother said the baby was healthy, the baby was moving strongly, there were no signs of infection and the baby was breastfeeding well. Midwifery care is provided in the form of providing care for newborns, umbilical cord care and providing IEC mothers with the importance of exclusive breastfeeding. Based on the care of newborns carried out at By. It was found that poor treatment of healthy newborns can cause abnormalities that can result in lifelong disabilities, even death. The conclusion is that the care provided was carried out well and produced positive results. It is hoped that the results of this case study can become a reference, and can develop knowledge regarding midwifery care for normal newborn babies.